Investigating the Caregiver Burden and Related Factors in Parents of 4 to 12 Years Old Children With Down Syndrome Living in Tehran City, Iran, in 2020 - Hossein Alibakhshi; Karim Ayoubi Avaz; Zahra Azani; Zahra Ahmadizadeh; Monia Siminghalam; Seyed Abolfazl Tohidast (University of Social Welfare and Rehabilitation Sciences, 2022)
Objective Having a child with a disability profoundly affects the family and can impose many problems and challenges on parents. Children with Down syndrome (DS) are a large group with special needs at risk for chronic physical illness, developmental problems, and behavioral and emotional problems. These problems create more health and care needs in these children. Therefore, the present study aimed to investigate the caregiver burden and related factors in parents of 4 to 12 years old children with DS living in Tehran City, Iran, in 2020. Materials & Methods In this cross-sectional study, 150 parents (91 females and 59 males) of children with DS participated. They were referred to rehabilitation centers and Down Syndrome Center in Tehran City, Iran, and were selected using a convenience sampling method. The demographic information questionnaire and Novak caregiver burden questionnaire (1989) were used to collect the study data. The participants were asked to complete these questionnaires carefully. The non-parametric tests, including the Mann-Whitney U, Kruskal-Wallis, and Spearman correlation tests, were used to analyze the data in SPSS v. 21 software. Results Based on data analysis, the Mean±SD age of the parents was 38.78±7.92 years. Sixty percent of children with DS were boys, and 40% were girls with a Mean±SD age of 7.14±2.38 years. The mean and standard deviation of the total parental care burden score and its subscales were as follows: overall care burden, 68.12±17.51; temporal care burden, 15.95±5.2; developmental care burden, 15.46±4.84; mental care burden, 12.22±4.85; physical care burden, 11.24±4.47; and social care burden, 11.18±4.94. There was a significant relationship between care burden and the following variables: age of parents (r=-0.66, P=0.001), parents' income (r=-0.6, P=0.001), number of children (r=0.55, P=0.001), and age of the child (r=0.6, P=0.001). While factors such as parents' gender, child gender, parents' marital status, receiving special education, care needs, and care status did not affect the amount of parental care burden (P>0.05). Conclusion The results of the present study showed that parents of children with DS experience moderate care burden in caring for their child. The findings of this study provide the opportunity for relevant government agencies, specialists, and health centers to understand the needs of children with DS and their parents at different stages of the disease, treatment, and care. So they can develop appropriate strategies to reduce the caring stress of their caring parents.